Development and application of an economic model (EQUIPTMOD) to assess the impact of smoking cessation. (14th September 2017) - Coyle, Kathryn; Coyle, Doug; Lester‐George, Adam; West, Robert; Nemeth, Bertalan; Hiligsmann, Mickael; Trapero‐Bertran, Marta; Leidl, Reiner; Pokhrel, Subhash; ,
Abstract: Background and Aims: Although clear benefits are associated with reducing smoking, there is increasing pressure on public health providers to justify investment in tobacco control measures. Decision‐makers need tools to assess the Return on Investment (ROI)/cost‐effectiveness of programmes. The EQUIPT project adapted an ROI tool for England to four European countries (Germany, the Netherlands, Spain and Hungary). EQUIPTMOD, the economic model at the core of the ROI tool, is designed to assess the efficiency of packages of smoking cessation interventions. The objective of this paper is to describe the methods for EQUIPTMOD and identify key outcomes associated with continued and cessation of smoking. Methods: EQUIPTMOD uses a Markov model to estimate life‐time costs, quality‐adjusted life years (QALYs) and life years associated with a current and former smoker. It uses population data on smoking prevalence, disease prevalence, mortality and the impact of smoking combined with associated costs and utility effects of disease. To illustrate the tool's potential, costs, QALYs and life expectancy were estimated for the average current smoker for five countries based on the assumptions that they continue and that they cease smoking over the next 12 months. Costs and effects were discounted at country‐specific rates. Results: For illustration, over a life‐time horizon, not quitting smoking within the next 12 months in England will reduce life expectancy by 0.66, reduce QALYs by 1.09 and result in £4961 higher disease‐related health care costs than if the smoker ceased smoking in the next 12 months. For all age–sex categories, costs were lower and QALYs higher for those who quit smoking in the 12 months than those who continued. Conclusions: EQUIPTMOD facilitates assessment of the cost effectiveness of smoking cessation strategies. The demonstrated results indicate large potential benefits from smoking cessation at both an individual and population level.